Revisiting the interleukin 17 family of cytokines in psoriasis: pathogenesis and potential targets for innovative therapies - Brembilla, Nicolo Costantino; Boehncke, Wolf-Henning (Frontiers in Immunology, 2023)
Psoriasis is a common chronic inflammatory skin disease, associated with substantial comorbidity. TH17 lymphocytes, differentiating under the influence of dendritic cell-derived IL-23, and mediating their effects via IL-17A, are believed to be central effector cells in psoriasis. This concept is underlined by the unprecedented efficacy of therapeutics targeting this pathogenetic axis. In recent years, numerous observations made it necessary to revisit and refine this simple “linear” pathogenetic model. It became evident that IL-23 independent cells exist that produce IL-17A, that IL-17 homologues may exhibit synergistic biological effects, and that the blockade of IL-17A alone is clinically less effective compared to the inhibition of several IL-17 homologues. In this review, we will summarize the current knowledge around IL-17A and its five currently known homologues, namely IL-17B, IL-17C, IL-17D, IL-17E (also known as IL-25) and IL-17F, in relation to skin inflammation in general and psoriasis in particular. We will also re-visit the above-mentioned observations and integrate them into a more comprehensive pathogenetic model. This may help to appreciate current as well as developing anti-psoriatic therapies and to prioritize the selection of future drugs’ mode(s) of action.